Changing Patterns of Relationships Between Geographic Markers and IBD: Possible Intrusion of Obesity. Issue 2 (3rd June 2020) - Szilagyi, Andrew; Smith, Brian E; Sebbag, Natanel; Leighton, Henry; Xue, Xiaoqing
Abstract: Background: Latitude and lactase digestion status influence incidence and prevalence rates of some noncommunicable diseases. Latitudinal correlations helped define beneficial roles of vitamin D in many diseases like inflammatory bowel disease (IBD). In view of recent global expansion of IBD and population migrations, we reexamine relations with these markers. As these changes also paralleled the pandemic of obesity, we explore possible interactions with IBD. Methods: We undertook a literature review to compare rates of obesity, Crohn's disease and ulcerative colitis with the geographic markers of lactase digestion status, average population-weighted national latitude, and national yearly sunshine exposure. Pearson correlations were used throughout to determine r correlation factors. Statistical significance was accepted at P <0.05 using 2-tailed tests. Results: Forty-seven countries were matched with various data sets that could be analyzed (range of availability was 49%–85%). While global correlations of IBD with latitude and lactase status remain similar to previous analyses, in Europe and Asia, outcomes were different. Global outcome contains a statistical paradox related to combining countries from Europe and Asia. Obesity showed moderate global correlations with IBD but weak and negligible correlations in Europe and Asia. There was also a weak global correlation with latitude. Conclusions: It is suggested that global correlations point to parallel geographic spread of IBD and obesity. The lack of latitudinal relations with obesity suggests reduced vitamin D effect. The paradox supports epidemiological differences in western and eastern IBD. Obesity combined with IBD may contribute to different relations, partly due to variable vitamin D effects. Lay Summary: Two ecological markers have defined lower national rates of inflammatory bowel disease (IBD). Both low latitudes and high population lactose maldigestion frequencies were associated. These associations have changed due to global extension of IBD, immigration, and parallel obesity. Observed regional differences may be impacted by obesity rates.